MAPPING SEASCAPES TOURISM DESTINATION IN INDONESIA - Ismayanti, Ismayanti (Universitas Sahid, 2018)
This research was to map prospective seascapes tourism destination. As results, some challenges occurred in seascapes destination development. Thus, it can be concluded that main activities of seascapes tourism are: cruising, yachting, surfing, leisure fishing and watersport activities i.e. Jet skiing. The development of seascapes tourism destination falls into: (1) Pioneering phase takes place in new-found attraction that it is recently built and has potential tourists; (2) Expansion stage occurred in areas that already exist with certain service quality level and loyal customer; (3) Improvement phase, the area is mature and ready-visit; and (4) Revitalization for saturated destination. It was recommended that marine infrastructure and tourist facilities such as: floating pontoons and dinghy-jetty, F&B establishment and toilet must be constructed. Brand awareness and market penetration are created. Evaluations on existing activities and attractions as well as maintenance of infrastructure, networking and hard-selling act were needed. Sharpen competitive advantages, sustainable marketing strategy; maintain loyalties of tourist, infrastructure and facilities as well as networking are a must. Feature of attraction and activities should be modified, re-adjustment based on tourist’s preference and re-orientation on networking when destination reach revitalization phase.